Analisis Gaya Kepemimpinan Terhadap Kinerja Karyawan CV. Mutiara - Syuryatman Desri; Nadra Nadila Hutasuhut (Concept: Journal of Social Humanities and Education, 2023)
This study aims to find out how the leadership style applied by the leaders of CV. Mutiara uses observation techniques, literature studies and interviews with CV leaders. Pearl. This kind of research is qualitative in nature. The results of the research show that the leader of CV. Mutiara applies a democratic and participative leadership style. Leader CV. Mutiara wants to improve staff performance with every employee in CV. Mutiara is valued for her potential and the company often organizes events or activities intended to raise performance standards among its employees.